Effect of Fraud Management Practices on Non- Financial Performance of Selected Deposit Money Banks in Lagos State, Nigeria: Array - Fakunmoju, Segun; Olukayode, Fasola (The Journal of Accounting and Management, 2021)
The increasing trend of declined in non-financial performance of banks in recent years pose serious threats to the stability and survival of financial and real sectors and banks in particular. Studies have shown that most deposit money banks in Nigeria have experienced declined in non-financial performances due to poor fraud management practices which have resulted in financial losses to banks and loss of public confidence in the banking sector. The study found out that fraud management practices have positive and significant effect on bank efficiency and operational performance of the selected deposit money banks with (P<5%). The study concluded that fraud management practices have effect on bank operational performance and efficiency deposit money banks in Lagos State, Nigeria. The study recommended that management of banks should exert collective efforts in identifying the ideal mix of effective and efficient fraud management practices that matches their banking business scope so as to achieve targeted operational performance and bank efficiency.